Role of vitamin D metabolism in cutaneous tumour formation and progression - Nemazannikova, N.; Antonas, K.; Dass, Crispin (John Wiley & Sons Ltd., 2013)
Objectives:  Very limited information is available on the role of vitamin D in skin carcinogenesis. For most individuals, skin cancer can be readily managed with surgery; however, some patients may face life-threatening neoplasia. Sun exposure, specifically UV radiation, is a causative agent for development of skin cancer, though, somewhat ironically, sunlight through the production of vitamin D may have protective effect against some skin cancers. This review focuses on the development and progression of cutaneous carcinogenesis and the role of vitamin D in the prevention of the initiation and progression of lethal skin cancers.Key findings:  Vitamin D is involved in regulation of multiple signalling pathways that have implications in carcinogenesis. Skin cancer metastasis depends on the tumour microenvironment, where vitamin D metabolites play a key role in prevention of certain molecular events involved in tumour progression. The vitamin D receptor (VDR) is a well-known potent regulator of cellular growth and differentiation.Summary:  The VDR's possible involvement in cell death, tumour microenvironment and angiogenesis makes it a candidate agent for cancer regulation.